Comparative Identification of Mycobacterium bovis By Using A Serological ELISA (IDEXX) and Tuberculin Test in Cattle in Wasit Province /Iraq - SR. AL-Taee, Hala (Journal of College of Education, 2018)
In Iraq, due to semi-full-scale dependence on tuberculin test, and presence, only, limited serological and molecular studies, the practical Mycobacterium bovis infection rate still dispersed especially in Wasit province that consider as an endemic area for bovine tuberculosis. In this study, two diagnostic techniques were used, IDEXX ELISA and tuberculin test; 186 cattle (155 females and 31 males), selected randomly and divided into two age groups, the first with less than 5 years and the second with more than 5 years. All cattle submitted to both tests and the results showed that (9.13%) were positives for tuberculin test and (17.2%) for IDEXX ELISA. Also, in age groups, the result of <5 years group by tuberculin test was 5.04%, and 11.76% by IDEXX ELISA test; while in >5 years group, was 16.41% and 26.86%, by tuberculin test and IDEXX ELISA test, respectively. Significant, the statistical different, P£ 0.05, was reported through the positive results of both tests as well as the two age groups, while in sex groups, the variance had not shown through both sexes.